Effects of boron deficiency on the metabolism in tomato root tips - Machado, Marcos A.; Gomes, Maria Mercês de S. (Pesquisa Agropecuaria Brasileira, 2014)
Variations in growth, total soluble sugars, mono and polyphenols, proteins and ribonucleic acids were studied in root tips of tomato (Lycopersicon esculentum Mill. cv. Campbell 33) submitted to boron deficiency for 0, 2, 4, and 6 days. From the second day onwards, boron deficiency reduced growth of the plants and also the concentration of total soluble sugars (a fact probably associated with the increased synthesis of structural material) and monophenols (a phenomenon associated to the increased oxidation of these compounds). Polyphenols, proteins and RNA were increased in the boron-deficient root tips. Boron may act more directly on the ribonucleic acid metabolism than on protein metabolism.